What are the dangers of biological therapy discontinuation or dose reduction strategies when treating rheumatoid arthritis?. Issue 11 (1st November 2016) - Atzeni, Fabiola; Benucci, Maurizio; Talotta, Rossella; Masala, Ignazio Francesco; Sarzi-Puttini, Piercarlo; Govoni, Marcello
ABSTRACT: Introduction: Treatment with biological DMARDs (bDMARDs) has meant that remission or low disease activity (LDA) is now a realistic goal for patients with rheumatoid arthritis (RA). However, as in the case of all long-term therapies, potential side-effects give rise to concern. The main reasons for withdrawing or tapering bDMARDs are safety and the sustainability of national healthcare systems. Given these data our review has been focused on important question: whether conventional, including steroids, or bDMARDs can be reduced or even stopped in patients with stable established RA or early RA. Areas covered: The studies included in the evaluation had to be RCTs, observational studies, systematic reviews evaluating the withdrawing or tapering bDMARDs in RA patients who have been on long-term treatment and have achieved remission or LDA. A search was made in the MEDLINE and EMBASE databases from 1980 to May 2016. Expert commentary: There is curently no standardised way of identifying the patients for whom reducing bDMARD therapy is appropriate. Clinical experience and data from de-escalation studies suggest that patients with RA in sustained remission are the best target population for studying drug-tapering regimens, and that LDA should not be considered an adequate indication for bDMARD de-escalation because it could hide a persistent amount of inflammation.